Oral Prednisolone vs. IM Corticotropin and Hypsarrhythmia* in West Syndrome - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at University of Columbo, Sri Lanka, studied the efficacy of oral prednisolone (40-60 mg/day) and intramuscular adrenocorticotrophin hormone (40-60 IU synthetic ACTH every other day) for 14 days in improving hypsarrhythmia in children (age 2 mos-2 yrs) with previously untreated West syndrome.